Performative Governance. (23rd October 2020) - Ding, Iza
ABSTRACT: The state often struggles to meet citizens' demands but confronts strong public pressure to do so. What does the state do when public expectations exceed its actual governing capacity? This article shows that the state can respond by engaging in performative governance—the theatrical deployment of language, symbols, and gestures to foster an impression of good governance among citizens. Performative governance should be distinguished from other types of state behavior, such as inertia, paternalism, and the substantive satisfaction of citizens' demands. The author illustrates this concept in the realm of environmental governance in China. Given the severity of China's environmental pollution, the resulting public outcry, and the logistical and political challenges involved in solving the problem, how can the state redeem itself? Ethnographic evidence from participant observation at a municipal environmental protection bureau reveals that when bureaucrats are confronted with the dual burdens of low state capacity and high public scrutiny, they engage in performative governance to assuage citizens' complaints. This study draws attention to the double meaning of "performance" in political contexts, and the essential distinction between the substantive and the theatrical.